Analisis SWOT pada Pelaksanaan Kegiatan Pemilihan Pustakawan Berprestasi Terbaik Tingkat Nasional di Masa Pandemi COVID-19 - Kamilah Kinanti; Novi Herwati (Media Pustakawan, 2022)
Selection of the Best Outstanding Librarian at the National Level is one way to appreciate librarians who are highly dedicated to their duties. This event is carried out by the National Library of Indonesia through the Center for Librarian Development in a systematic and tiered manner, starting from the election at the provincial level to the national level. The COVID-19 pandemic brought a different color to the Selection of National Best Outstanding Librarian year 2020, which was held online for the first time. Through this study, it provides an overview of the differences in the offline and online selection process for Outstanding Librarians, as well as a SWOT strategy analysis for each mechanism. The studywas conducted with a descriptive qualitative approach. Data collection is done by document review and observation, analysis is done by SWOT analysis. The results obtained the portrait of the change in the mechanism for the Selection ofOutstanding Librarians, where the online selection process is fully carried out via the virtual meeting application and eliminating of visit activities. Meanwhile, in the SWOT analysis, the results obtained are the ST strategy on the offline mechanism and the WO strategy on the online mechanism.